The Effect of Wages on Job Vacancy Duration: Evidence from a Spatial Discontinuity - Charles Carter; Judith M. Delaney; Kerry L. Papps (Institute of Labor Economics (IZA), 2024)
We exploit a spatial discontinuity in the wages paid by the United Kingdom's National Health Service to examine how wages affect the duration of time a vacancy is advertised. NHS workers in inner London are mandated by law to be paid an extra 4.3% more than those who work in outer London. We use a regression discontinuity design and estimate an elasticity of duration with respect to wages of -6.3. This number is larger than reported by previous studies and suggests that firms can fill worker shortages faster by raising wages. This also highlights the importance this margin of worker recruitment when analysing firm search and job match. Our results are robust to various checks including a placebo test using fictitious borders and are robust to changes in the bandwidth and the duration measure. The estimates are similar across all occupational groups in the NHS and are not limited to jobs that require specific skills such as nurses and therapists. Our results provide evidence for policy makers which suggests that increasing the wages paid to NHS workers may lead to increased cost savings by reducing the need to hire expensive agency staff and may also lead to better health outcomes of the population through reduced staff shortages.
Keywords: J22; J23; J31; J38; 330; vacancy duration; wages; employer search